Anaerobic oxidation of methane coupled with extracellular electron transfer to electrodes - Yaohuan Gao (Nature Portfolio, 2017)
Abstract Anaerobic oxidation of methane (AOM) is an important process for understanding the global flux of methane and its relation to the global carbon cycle. Although AOM is known to be coupled to reductions of sulfate, nitrite, and nitrate, evidence that AOM is coupled with extracellular electron transfer (EET) to conductive solids is relatively insufficient. Here, we demonstrate EET-dependent AOM in a biofilm anode dominated by Geobacter spp. and Methanobacterium spp. using carbon-fiber electrodes as the terminal electron sink. The steady-state current density was kept at 11.0 ± 1.3 mA/m2 in a microbial electrochemical cell, and isotopic experiments supported AOM-EET to the anode. Fluorescence in situ hybridization images and metagenome results suggest that Methanobacterium spp. may work synergistically with Geobacter spp. to allow AOM, likely by employing intermediate (formate or H2)-dependent inter-species electron transport. Since metal oxides are widely present in sedimentary and terrestrial environments, an AOM-EET niche would have implications for minimizing the net global emissions of methane.